2020
DOI: 10.1016/j.jot.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Promoting osteoblasts responses in vitro and improving osteointegration in vivo through bioactive coating of nanosilicon nitride on polyetheretherketone

Abstract: Objective To enhance the bioactivity of polyetheretherketone (PEEK) while maintain its mechanical strengths. Methods Suspension coating and melt bonding. Results Silicon nitride (Si 3 N 4 , SN) coating lead to higher surface roughness, hydrophilicity and protein absorption; SN coating could slowly release Si ion into simulated body fluid (SBF), which caused weak alkaline of micro-environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…To test and evaluate the biocompatibility of samples, we cultured further rat adipose stem cells on the G-DLPUs to observe the attachment and proliferation of cells [ [32] , [33] , [34] ]. All materials were treated in ultraviolet-sterilized biosafety cabinet before use.…”
Section: Methodsmentioning
confidence: 99%
“…To test and evaluate the biocompatibility of samples, we cultured further rat adipose stem cells on the G-DLPUs to observe the attachment and proliferation of cells [ [32] , [33] , [34] ]. All materials were treated in ultraviolet-sterilized biosafety cabinet before use.…”
Section: Methodsmentioning
confidence: 99%
“…In the attempt to find new alternatives that could be developed into effective, environmentally safe agrochemicals, we have investigated the ability of silicon nitride (Si 3 N 4 ), to knockdown P. viticola starting early in its infection cycle. The choice of this ceramic was based on its unique surface chemistry within an aqueous environment (Pezzotti, 2019) and its antibacterial (Pezzotti et al, 2018), antiviral (Pezzotti et al, 2020) and antifungal properties (Pezzotti, under review) while still being harmless to humans and widely used as a new therapeutic bioceramics in osteoarthropathy (Pezzotti et al, 2017;Dai et al, 2019;Calvert et al, 2020). Here we explore the possibility to consider Si 3 N 4 ) as a possible alternative for grapevine protection against P. viticola.…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria were generally negatively charged; thus, the interaction of negatively charged bacteria with positively charged –NH 3 + groups on SN could lead to disruption and lysis of the bacterial membrane [ 22 , 23 , 25 ]. Furthermore, the dissolution of SN could cause a weak alkaline microenvironment, which inhibited bacterial growth [ 25 , 28 , 37 ]. In this study, our results also demonstrated that both SNP and STP created a weak alkaline solution after soaking in SBF.…”
Section: Discussionmentioning
confidence: 99%